Effects of Antrodia Camphorata Mycelia Extract Containing Antroquinonol on Lowering Low-Density Lipoprotein Cholesterol: A Randomized Double-Blind Study - Miles Chih-Ming Chena,; Pei-Ni Chena,; Howard Hao-Yu Chenga,; Wayne Ching-Cheng Weia,; Ryuji Takedab,; Mitsuko Moric ,; Kiichiro Mochidad, (Journal of Pharmacy and Nutrition Sciences, 2017)
Objective: Antrodia camphorata is a type of true fungus that grows only on Cinnamomum camphora trees, also known as Cinnamomum kanehirae (“kashi”) in Taiwan. Antroquinonol is a characteristic component of A. camphorata mycelia extract and was previously shown to exhibit antitumor action and lower blood cholesterol (total cholesterol and low-density lipoprotein [LDL] cholesterol) in cellular and animal models. So, This study examined the ability of A. camphorata mycelia extract to reduce LDL cholesterol in humans. Methods: We conducted a randomized double-blind trial in 26 subjects with either borderline LDL cholesterol (120–139 mg/dL; n = 11) or mildly elevated LDL cholesterol (140–159 mg/dL; n = 15). Participants ingested tablets containing either 25 mg of A. camphorata mycelia extract (antroquinonol: 0.68 mg; n = 14) or a placebo (n = 12) for 12 weeks. Results: The test group showed a significant reduction in LDL cholesterol when compared with the placebo group after 12 weeks of tablet ingestion (p < 0.05), demonstrating the effects of A. camphorata mycelia extract on LDL cholesterol. A. camphorata mycelia extract also tended to reduce total cholesterol when compared with the placebo (p < 0.10). The borderline LDL cholesterol and mildly elevated LDL cholesterol subgroups showed a significant reduction in LDL cholesterol in subjects who ingested A. camphorata mycelia extract compared with those who ingested the placebo, again demonstrating the LDL cholesterol-lowering effect of the extract. Conclusion: A. camphorata mycelia extract lowers LDL cholesterol in individuals with somewhat high LDL cholesterol levels. This clinical trial was registered with the University Hospital Medical Information Network (UMIN no. # 000019670).